“Metaphors We Live by”: intertextual transformations - Budaev, Edward V.; Chudinov, Anatoly P. (Respectus Philologicus, 2006)
This article reviews a number of works and titles that which contain intertextual references to G. Lakoff and M. Johnson's well-known book on metaphors. The authors both introduce various cognitive researche of theoretical and practical value to readers and analyse five types of intertextual transformations of the title "Metaphors We Live By":1) noun-transformation;2) pronoun-transformation; 3) verb-transformation;4) preposition-transformation;5) expansion.